Cross-cultural psychiatry and depression in China: a clinical report - Moreno, Nicole (Revista del Hospital Italiano de Buenos Aires, 2022)
The following work presents the history of a 19-year-old patient from China who was hospitalized in a psychiatric ward of a general hospital due to a depressive illness, being the case remarkable for the polymorphism in the clinical symptoms that she presented. The objective is to analyze the need for an interdisciplinary approach that treats culture as a significant variable in the construction of a disease, understanding that pathophysiological models are necessary but not sufficient to comprehend how they are constituted. For this purpose, a brief review will be made of the studies carried out in the 1980s in China by the psychiatrist and anthropologist Arthur Kleiman and the perspective of the psychoanalyst Lunazzi Helena, who in her book “Alexithymia” develops how culture influences the verbal expression of emotions.
Keywords: psychiatry; culture; depression; China; alexithymia; neurasthenia